Vincent Lunardi, Esquire - Cosway, Richard; Bartolozzi, Francesco (Tufts Archival Research Center, 2008)
This illustration is from Charles Knight's "London," Vol. 6. This image was inserted by Edwin C. Bolles and is not found in the original. Subtitle reads, "Secretary to the Neopolitan Ambassador, and the first aerial traveller in the English atmosphere. Sept. 15, 1784."